Prebiotic, antioxidant and anti-inflammatory properties of edible Amazon fruits - Curimbaba, T. F.S. [UNESP]; Almeida-Junior, L. D. [UNESP]; Chagas, A. S. [UNESP]; Quaglio, A. E.V. [UNESP]; Herculano, A. M.; Di Stasi, L. C. [UNESP] (Elsevier, 2020)
Dietary products with prebiotic and antioxidant properties may be used to protect against chronic diseases, including inflammatory bowel diseases. Assai berry, burity palm and cupuassu from the Amazon are functional foods because of their high level of dietary fiber and polyphenols, which have an important role in the prevention of inflammatory processes. Their activity as a dietary supplement was measured using fruit pulp flours in a trinitrobenzenesulphonic acid model of intestinal inflammation. The intestinal anti-inflammatory effects were evaluated using clinical parameters and biochemical analysis of pro-inflammatory cytokines (IL-6, IL-1β and TNF-α), whereas antioxidant activity was studied using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, mieloperoxidase (MPO) and alkaline phosphatase (ALP) activities, glutathione (GSH) level and phenolic content. The effects of dietary supplementation on the mucin release and short-chain fatty acid (SCFA) production were studied. Assai berry and burity palm reduced MPO and ALP activities, counteracted GSH and propionate reductions induced by the inflammatory process as well as decreased IL-6, IL-1β and TNF-α levels and increased mucin production. Cupuassu reduced MPO and ALP activities, IL-6 and IL-1β levels and increased colonic mucin, without effects on the SCFA production and TNF-α colonic level. In vitro studies showed the antioxidant properties, which were associated with the presence of polyphenol compounds and scavenging activity using the DPPH assay. The results indicated the possible benefits of using assai berry and burity palm fruits as dietary antioxidant, prebiotic, immune modulators and anti-inflammatory complementary products to treat intestinal inflammation.
Keywords: Euterpe oleracea; Inflammatory bowel disease; Mauritia flexuosa; Polyphenol; Short-chain fatty acid; Theobroma grandiflorum